Preserving the Credibility of the Physician Peer Review System - Gharagozloo, Farid; Gruessner, Rainer; Postopm, Robert (International Journal of Innovative Research in Medical Science, 2023)
A just, equitable, and credible peer review process is the cornerstone of a high quality and safe Health Care System. The importance of an unbiased and protected Peer Review System is codified in the Health Care Quality Improvement Act of 1986, HCQIA. However, the peer review process may go wrong when in the new landscape of healthcare which is dominated by large hospital organizations and the big business of medicine, the peer review system may be misused for reasons other than to ensure compliance to the highest standards of professionalism in the interest of the public and the profession. In those instances, due to the immunity protection, which is afforded by HCQIA, contrived allegations of incompetence or disruptive behavior may be used to retaliate against physicians. Most physicians are not familiar with these complex issues which can affect their careers. It is time for a comprehensive discourse among physicians and healthcare attorneys with the singular goal of preserving the legitimacy of Peer Review.